Academic Case Managers: Supporting the Educational Life of Urban Middle School Students of Poverty - Nancy Van Kannel-Ray; Warren E. Lacefield; Pamela J. Zeller (The Evaluation Center at Western Michigan University, 2008)
For the past eight years, Midwest Educational Research Consortium (MERC), located at Western Michigan University, received two multi-million dollar grants through a U.S. Department of Education program entitled Gaining Early Awareness and Undergraduate Programs (GEAR UP). GEAR UP is a school/university partnership using a cohort model with the goal of increasing the number of students of poverty who graduate from high school and go on to post secondary education.The MERC/GEAR UP project partners with two universities, two community colleges, and four school districts in Michigan and Ohio.